Double-hit primary unilateral adrenal lymphoma with good outcome - Marković, Olivera; Marisavljević, Dragomir; Jelić, Svetlana; Mihaljević, Biljana; Martinović, Taamara; Čemerikić, Vesna (Vojnosanitetski pregled, 2014)
Introduction. Primary adrenal non-Hodgkin’s lymphoma (NHL) is a rare neoplasm with poor prognosis. On the other side, double-hit lymphomas with BCL2 and MYC translocation are characterized by advanced disease stage, extranodal and central nervous system involvements at presentation or disease progression. Case report. We reported a 73-year-old male patient with double-hit primary adrenal lymphoma and preserved adrenal function, showing a favorable clinical course. Computed tomography of abdomen showed a 9 ´ 7 cm mass of the left adrenal gland. Laparatomy with left adrenalectomy was done and histological examination revealed diagnosis of a diffuse large B-cell NHL (DLBCL), non-GCB subtype. The patient was treated with 6 cycles of R-CHOP chemotherapy with reduced doses of doxorubicin because of the decreased left verticle ejection fraction. The patient was followed up regularly for 20 months with no evidence of tumor recurrence despite the inherently poor prognostic profile and double-hit phenotype of the disease. Conclusion. R-CHOP chemotherapy in combination with adrenalectomy can be an effective first-line regimen for primary adrenal DLBCL, despite the inherently poor prognostic profile (non-GCB subtype, bulky disease, elevated lactate dehydrogenase and double-hit phenotype of the disease).